Analisis Pengaruh Orientasi Pelanggan, Keahlian, Kualitas Makanan, Kewajaran Harga, Dan Lingkungan Fisik Terhadap Kualitas Hubungan (Studi Empiris di Rumah Makan Mang Engking dan Rasa Mirasa) - Arianti, Yasela Dias; , Dr. Soepatini, M.Si (2017)
The purpose of this study is to analyze the effect of customer orientation, expertise, food quality, price fairness, and the physical environment to the relationship quality restaurant MangEngking and Rasa Mirasa. Data is collected using a questionnaire instrument or questionnaire. This study the researchers used a technique Non-Probability Sampling. While the sampling technique using purposive sampling of 98 consumers who come to the restaurant MangEngking and Rasa Mirasa defined based on specific criteria researchers.The analysis of data obtained in the form of quantitative and qualitative analysis. A quantitative analysis includes the validity and reliability test, the classic assumption test, multiple regression analysis test, F test, t test, and analysis of the coefficient of determination (R2). The qualitative analysis constitutes interpretation of the data which have been collected in this study before and the results of processing data have been implemented by providing descriptions and explanations.. The results of this study indicate that all independent variables are customer orientation, expertise, food quality,price fairness, and the physical environment together positive and significant impact on the relationship quality restaurant MangEngking and Rasa Mirasa, where the physical environment is the mostdominant variable.